2010
DOI: 10.1039/c0nr00095g
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of doping on thermal and thermoelectric properties of nanomaterials

Abstract: Thermal transport in nanoscale structures has attracted an increasing interest in the last two decades. On the one hand, the low dimensional nanostructured materials are platforms for testing novel phonon transport theories. On the other hand, nanomaterials are promising candidates for nanoscale on-chip coolers. This review is focused on the thermal conductance, thermoelectric property, and impacts of doping on these properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
83
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 149 publications
(91 citation statements)
references
References 130 publications
(157 reference statements)
7
83
0
1
Order By: Relevance
“…However, the experimentally observed 20% reduction in thermal conductivity is interesting to compare with the reduction obtained in other silicon-based nanostructures. On one hand, a stronger reduction was measured in silicon with pores (>50%) [9,18,19], nanodots (>70%) [13,68], polycrystalline grains (>80%) [15,69,70], dopants (>50%) [71,72] or germanium atoms (>70%) [14,71,73]. On the other hand, the 20% reduction by the pillars [63] is comparable to the reduction by holes (20–25%) [21,74] or slits (20–30%) [75] covering the same relative area.…”
Section: Experimental Measurements Of the Thermal Propertiesmentioning
confidence: 99%
“…However, the experimentally observed 20% reduction in thermal conductivity is interesting to compare with the reduction obtained in other silicon-based nanostructures. On one hand, a stronger reduction was measured in silicon with pores (>50%) [9,18,19], nanodots (>70%) [13,68], polycrystalline grains (>80%) [15,69,70], dopants (>50%) [71,72] or germanium atoms (>70%) [14,71,73]. On the other hand, the 20% reduction by the pillars [63] is comparable to the reduction by holes (20–25%) [21,74] or slits (20–30%) [75] covering the same relative area.…”
Section: Experimental Measurements Of the Thermal Propertiesmentioning
confidence: 99%
“…Doping with isotopes atoms increases phonon scattering, thus results in reduction of thermal conductivity. 29 In 2008, Yang, Zhang and Li investigated the isotopic effect on thermal conductivity of SiNWs. 79 As shown in Fig.…”
Section: A 1d Nanostructuresmentioning
confidence: 99%
“…Compared to the single component NWs, the physical properties of core-shell NWs can be further tailored by different compositions and different configurations, thus leading to various novel nanoscale electronic and optoelectronic devices [1][2][3]. In addition to the electronic and optical properties, thermal property of NWs has attracted more and more interests due to the potential thermoelectric applications in both power generation and refrigeration [4]. For instance, by etching the surface of silicon NWs, it has been experimentally demonstrated that thermal conductivity of Si NW can be reduced more than two orders of magnitude compared with bulk Silicon [5,6].…”
mentioning
confidence: 99%